Prospective randomized trial of hexylaminolevulinate photodynamic‐assisted transurethral resection of bladder tumour (TURBT) plus single‐shot intravesical mitomycin C vs conventional white‐light TURBT plus mitomycin C in newly presenting non‐muscle‐invasive bladder cancer. (4th November 2013) - O'Brien, Timothy; Ray, Eleanor; Chatterton, Kathryn; Khan, Muhammad Shamim; Chandra, Ashish; Thomas, Kay
Abstract : Objective: To determine if photodynamic 'blue‐light'‐assisted resection leads to lower recurrence rates in newly presenting non‐muscle‐invasive bladder cancer (NMIBC). Patients and Methods: We conducted a prospective randomized trial of hexylaminolevulinate (HAL) photodynamic diagnosis (PDD)‐assisted transurethral resection of bladder tumour (TURBT) plus single‐shot intravesical mitomycin C vs standard white‐light‐assisted TURBT plus single‐shot intravesical mitomycin C. A total of 249 patients with newly presenting suspected NMIBC enrolled at Guy's Hospital between March 2005 and April 2010. Patients with a history of bladder cancer were excluded. The surgery was performed by specialist bladder cancer surgical teams. Of the eligible patients, 90% agreed to be randomized. Results: Of the 249 patients, 209 (84%) had cancer and in 185 patients (89%) the cancer was diagnosed as NMIBC. There were no adverse events related to HAL in any of the patients randomized to the intravesical HAL‐PDD arm. Single‐shot intravesical mitomycin C was administered to 61/97 patients (63%) in the HAL‐PDD arm compared with 68/88 patients (77%) in the white‐light arm ( P = 0.04) Intravesical HAL was an effective diagnostic tool for occult carcinoma in situ (CIS). Secondary CIS was identified in 25/97 patients (26%) in the HAL‐PDD arm compared with 12/88 patients (14%) in the white‐light arm (( P = 0.04) There was no significant difference in recurrence between the two arms at 3 or 12 months: in the HAL‐PDD and the white‐light arms recurrence was found in 17/86 and 14/82 patients (20 vs 17%), respectively (( P = 0.7) at 3 months, and in 10/63 and 15/67 patients (16 vs 22%), respectively (( P = 0.4) at 12 months. Conclusions: Despite HAL‐PDD offering a more accurate diagnostic assessment of a bladder tumour, in this trial we did not show that this led to lower recurrence rates of newly presenting NMIBC compared with the best current standard of care.